2021
DOI: 10.1186/s12879-020-05689-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance awareness and antibiotic prescribing behavior among healthcare workers in Nigeria: a national survey

Abstract: Background Antimicrobial resistance (AMR) is a global problem compromising the effective treatment of infectious diseases. The World Health Organization (WHO) is encouraging and promoting awareness creation among health workers as one of its strategies to reduce the rate of emergence and transmission of AMR. Available data on the prescribing behavior of healthcare workers (HCWs) in Nigeria remains incomplete. This study was designed to provide an up-to-date estimate of the knowledge, attitude a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 21 publications
4
34
1
Order By: Relevance
“…This was also reported in a German study that assessed the effect of knowledge about antibiotic resistance on the prescribing pattern among practitioners; awareness about antimicrobial resistance highly influenced the practitioners' pattern in prescribing antibiotics to their patients, and this was confirmed in additional studies in Iran and Croatia [27][28][29]. Conversely, two studies in Cambodia and Nigeria found that physicians were alert about the challenge related to the misuse of antibiotics, but this did not influence their practice in managing antibiotic prescribing [30,31]. Understanding the factors associated with overprescribing of antibiotics including prescribers' knowledge is crucial to find strategies to overcome this challenge [32][33][34].…”
Section: Discussionmentioning
confidence: 69%
“…This was also reported in a German study that assessed the effect of knowledge about antibiotic resistance on the prescribing pattern among practitioners; awareness about antimicrobial resistance highly influenced the practitioners' pattern in prescribing antibiotics to their patients, and this was confirmed in additional studies in Iran and Croatia [27][28][29]. Conversely, two studies in Cambodia and Nigeria found that physicians were alert about the challenge related to the misuse of antibiotics, but this did not influence their practice in managing antibiotic prescribing [30,31]. Understanding the factors associated with overprescribing of antibiotics including prescribers' knowledge is crucial to find strategies to overcome this challenge [32][33][34].…”
Section: Discussionmentioning
confidence: 69%
“…Despite the potentially dire consequences of AMR on animal and public health in sub-Saharan countries, public awareness remains poor. Also, many professionals within the various One Health sectors are poorly aware of their role in ensuring antimicrobial stewardship (AMS) (11,12,(16)(17)(18). There is still a limited appreciation of collaborative planning and data sharing needed to guarantee an enhanced response to the challenge of suboptimal antibiotic use and to mitigate the spread of AMR.…”
Section: Low Level Of Awareness Of Amr Among the Public And Professionalsmentioning
confidence: 99%
“…At the heart of operationalising One Health is the need to mainstream AMR into other educational and public discussions that emphasise AMR management as a healthy public policy. Firstly, the country needs to rethink and reframe the way we communicate AMR especially due to poor understanding of AMR by the lay public and even among health professionals (16,17). The challenges AMR pose-including economic lossesneed to be presented as a problem of the present and the future, and communicated appropriately for adequate risk perception.…”
Section: Way Forwardmentioning
confidence: 99%
“…Antimicrobial resistance (AMR) is a global problem that puts the treatment of infectious diseases at risk [1]. It is hazardous to one's health and development [2].…”
Section: Introductionmentioning
confidence: 99%